What perspective? Which gender? From comprehensive sex education to minority stress (Praxis Educativa, 2021)
The “gender perspective” seems to be the key to solve a series of pressing problems on the most varied issues. All the expectations projected on it make it an unavoidable reference in certain academic and political contexts. On the other hand, its ontological assumptions, epistemological framework, and practical implications, which are the central themes of this work, have been scarce. Our aim is to raise some problemsof this perspective -as expressed in our context- and develop its scope. Following these axes, we will apply our considerations on the proposals of Comprehensive Sexual Education (ESI in Spanish). Our contention is that when we focus on the experiences of trans* people, the so-called “gender perspective” is all too oftenpart of the problem to be solved, rather than its solution.
Keywords: gender; sexual difference; cisexism; cisnormativity; minority stress